Enhanced Cycling Performance of Li‐O2 Batteries by the Optimized Electrolyte Concentration of LiTFSA in Glymes. Issue 4 (10th December 2012) - Li, Fujun; Zhang, Tao; Yamada, Yuki; Yamada, Atsuo; Zhou, Haoshen
Abstract A series of non‐aqueous electrolytes were prepared by dissolving lithium bis(trifluoromethylsulfonyl)amide (LiTFSA) in triglyme and tetraglyme (Gx, x = 3 and 4), respectively, with varied molar ratios. With the electrolytes the cycling performance of Li‐O2 batteries showed a strong dependence on the molar ratios between LiTFSA and Gx. It was found that the molar ratio of 1 to 5 was critical for the cycling‐performance of Li‐O2 batteries. High stability over 20 discharge–recharge cycles at 500 mA/gcarbon and in an O2 flow was obtained in LiTFSA‐(Gx)5 (x = 3 and 4). The discharge product at cathode could be directly detected and identified as the dominant crystalline product Li2O2 on the 1st and 20th discharged electrodes using X‐ray diffraction technique (XRD), which indicates rechargeability and feasibility of the electrolytes LiTFSA‐(Gx)5 (x = 3 and 4) for Li‐O2 batteries. At 1000 mA/gcarbon their capacities could be stabilized for 10 cycles. To our knowledge, this behavior of dependence of cycling performance of Li‐O2 batteries on the concentration of Li salts is presented here for the first time, and it may be extended to other Li salts and solvents and suggest a new route for screening cycling‐stable electrolytes for Li‐O2 batteries.